Ballet Clássico: O ensino pelo método da Royal no Espaço de Dança Movimentar, em Mosqueiro-PA - CARMO, Ana Milena Navegante (2023)
The present work consists in the analysis of the teaching of classical ballet based on the method of the Royal Academy of Dance applied to the students of the Moving Dance Space, on the Island of Mosqueiro- PA. I highlight my experiences as a dancer-teacher in this context of teaching-learning, bringing reports about the field research, which was carried out in 2020, from the examination of the 3rd degree of teaching of the English method of classical ballet, based on the basic theory of the studies of psychomotricity, according to the studies of Alves (2008).In order to achieve the desired objectives, theoretical references of classical dance were used, such as: Sampaio (2013) and Agostini (2010). Finally, I present the results of the evaluation process and the solemnity of delivery of the results of the examination, in order to emphasize the importance of teaching classical dance to the students of that context.